Pengaruh Media Sosial Instagram, Lokasi Dan Persepsi Harga Terhadap Keputusan Pembelian Pada Kawan Kofie Tebing Tinggi - Azman, Muhammad Richie; Putra, Tri Nugraha Basri; Purba, Rakhmawati; Victor, Victor (STIE Bina Karya, 2025)
This study aims to determine the Influence of Instagram Social Media, Location and Price Perception on Purchasing Decisions at Kawan Kofie in Tebing Tinggi City. The research method used is a quantitative method using the help of the SPSS version 25.00 program. The nature of the research used is replication. The sample of this study was 96 respondents, namely Kawan Kofie consumers in Tebing Tinggi City. The data collection method used was a questionnaire and literature study. The analysis method used in this study was using multiple linear regression analysis. The results of this study are Instagram social media influences purchasing decisions at Kawan Kofie, Location does not influence purchasing decisions at Kawan Kofie, Price perception influences purchasing decisions at Kawan Kofie and Instagram social media, location and price perception simultaneously influence purchasing decisions at Kawan Kofie.